Say-On-Pay Voting: The Moderating Roles of Executive Pay Misassessment and Pay-for-luck Compensation on CD&A Usefulness - Racharoenkit, Wichawadee; Jaikengkit, Aim-Orn (Creative Business and Sustainability Journal, 2024)
Although multiple studies have confirmed the instances of irrational Say-On-Pay (SOP) voting and pay-for-luck compensation, the assessment of executive compensation under these occurrences remained unrevealed prior to our research. This research attempts to address these limitations by defining irrational SOP voting and pay-for-luck variables and modifying the SOP voting determinants model, drawing on information-processing theory. The objectives are to investigate: the moderating effect of executive pay misassessment linked to irrational SOP voting and pay-for-luck compensation on CD&A usefulness, reflected by the association between excessive pay and SOP voting outcomes and the association between pay-performance sensitivity (PPS) and SOP voting outcomes, and shareholder awareness of pay-for-luck compensation, indicated by the association between pay-for-luck and SOP voting outcomes. The results show the significant moderating roles of executive compensation misassessment and pay-for-luck compensation on SOP voting outcomes and shed light on the unawareness of executive pay-for-luck. Overall, this study demonstrates a better explanation of SOP voting decisions through the lens of information-processing theory. Additionally, it provides new evidence of the PPS assessment concerning shareholders unawareness of pay-for-luck compensation.